Du nouveau sur 'Chrysostome et Chalkèdôn' - Devos, Paul (Analecta Bollandiana, 1995)
Both an article by D. V. Proverbio about the Ethiopic MS. Comboniano H3, in Orientalia (63 [1994], p. 57-67), and a catalogue by A. I. Elanskaya (The Literary Coptic MSS in the A. S. Pushkin State Fine Arts Museum in Moscow [= Supplements to Vigiliae Christianae, 18], Leiden, 1994) have shed some new light in 1994 on the Coptic Story of 'Chrysostom and Khalkedon' as studied before by T. Orlandi and P. Devos.